2022
DOI: 10.1111/jfpe.14241
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic modeling the survival of Escherichia coli in pickled radish fermentation with different salt concentrations

Abstract: The survival of Escherichia coli in pickled radish fermentation with salt concentrations from 2% to 10% was studied kinetically. The results showed that mostly E. coli first underwent 1–2 days of growth, followed by a decline and finally died off after 4–5 days of fermentation. A kinetic model was developed to reveal how the growth and survival of E. coli were affected by acid content, pH value and salt concentration during the pickle fermentation. Model‐based simulations suggested that moderate salt concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…High salt concentrations can inhibit the growth of putrefying bacteria, the formation of harmful chemicals and reduce the risk of spoilage, but can also lead to a reduction in the relative abundance of LAB, resulting in poor‐quality final products (Xiong et al ., 2016). In contrast, lower salt concentrations can increase the relative abundance of LAB, resulting in higher product quality and safety, by inhibiting E. coli growth (Wu et al ., 2023). A study on the effects of different salt concentrations on foodborne pathogenic E. coli O157:H7 and Listeria monocytogenes demonstrated that lower salt concentrations of 1% and 2% resulted in lower survival rates of pathogenic bacteria compared with 3% salt (Kim et al ., 2021).…”
Section: Variables That Influence Vegetable Fermentationmentioning
confidence: 99%
“…High salt concentrations can inhibit the growth of putrefying bacteria, the formation of harmful chemicals and reduce the risk of spoilage, but can also lead to a reduction in the relative abundance of LAB, resulting in poor‐quality final products (Xiong et al ., 2016). In contrast, lower salt concentrations can increase the relative abundance of LAB, resulting in higher product quality and safety, by inhibiting E. coli growth (Wu et al ., 2023). A study on the effects of different salt concentrations on foodborne pathogenic E. coli O157:H7 and Listeria monocytogenes demonstrated that lower salt concentrations of 1% and 2% resulted in lower survival rates of pathogenic bacteria compared with 3% salt (Kim et al ., 2021).…”
Section: Variables That Influence Vegetable Fermentationmentioning
confidence: 99%